Developmental Programming in Response to Maternal Overnutrition - Alfaradhi, Maria; Ozanne, Susan (Frontiers in Genetics, 2011)
Metabolic disorders have seen an increased prevalence in recent years in developed as well as developing countries. While it is clear lifestyle choices and habits have contributed to this epidemic, mounting evidence suggests the nutritional milieu during critical stages of development in early life can ‘program’ individuals to develop the metabolic syndrome later in life. Extensive epidemiological data presents an association between maternal obesity and nutrition during pregnancy and offspring obesity, and a number of animal models have been established in order to uncover the underlying mechanisms contributing to the programming of physiological systems. It is hard to distinguish the causal factors due to the complex nature of the maternal-fetal relationship; however, in order to develop adequate prevention strategies it is vital to identify which maternal factor(s) – be it the diet, diet-induced obesity or weight gain – and at which time during early development instigate the programmed phenotype. Curtailing the onset of obesity at this early stage in life presents a promising avenue through which to stem the growing epidemic of obesity.